The Administration of justice and the secret of summary before the media - Martínez Cristóbal, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Freedom of information is one of the rights inherent to human beings, but it is necessary to establish control limits to protect citizens. The judicial system is obliged to weigh the value of the right to information with that of the rights to privacy and even with the integrity of the judicial procedure itself. It is essential to reorient the attitude of journalism when reporting, due to the special seriousness of attacks against the confidentiality of the procedure or judicial impartiality.